(untitled) (Nativa, 2024)
A seca é o principal evento causado pela variabilidade climática, esses episódios aumentam em frequência, intensidade e duração no Brasil. O objetivo desse estudo é avaliar a distribuição anual e mensal da precipitação e tendências de acréscimos ou decréscimos e identificar eventos de secas meteorológicas e agrícolas para os municípios da região Oeste de Mato Grosso: Campo Novo do Parecis, Campos de Júlio, Comodoro e Sapezal. Os dados foram adquiridos via Google Earth Engine (GEE), e correspondem a reanálises ERA5-Land. Para avaliação das secas foi utilizado o Índice Padronizado de Precipitação-Evapotranspiração (SPEI). Para análise de tendência foi aplicado o teste não paramétrico de Man-Kendall. Nos quatro municípios há duas estações bem definidas, seca e chuvosa, com regime anual de precipitação semelhantes. A maior média anual de precipitação foi em Comodoro, bioma Amazônico, sendo os outros três do bioma Cerrado. É observada uma redução da precipitação anual nas últimas décadas em toda a região. No início do século XXI, houve maior acentuação de períodos secos, conforme a estatística Z do teste de Man-Kendall ocorreu redução significa da precipitação em maio, julho, agosto setembro e outubro. Os principais eventos de secas foram em 2015 a 2016 e 2019 a 2020 para as regiões. Palavras-chave: tendências; variabilidade climática; Índice Padronizado de Precipitação-Evapotranspiração. Analysis of precipitation and identification of drought events in municipalities in western Mato Grosso using SPEI-3 and SPEI-6 indices ABSTRACT: Drought is the primary event driven by climate variability, and these episodes are increasing in frequency, intensity, and duration in Brazil. This study aims to assess the annual and monthly distribution, as well as trends of increases or decreases in precipitation, and to identify meteorological and agricultural drought events for municipalities in the western region of Mato Grosso: Campo Novo do Parecis, Campos de Júlio, Comodoro, and Sapezal. Data were acquired via Google Earth Engine (GEE), utilizing ERA5-Land reanalysis. The Standardized Precipitation-Evapotranspiration Index (SPEI) was applied to assess droughts, and the Man-Kendall non-parametric test was used for trend analysis. All four municipalities experience two well-defined seasons, wet and dry, with similar annual precipitation patterns. Comodoro, located in the Amazon biome, recorded the highest annual precipitation averages, while the other three municipalities lie within the Cerrado biome. Over recent decades, annual precipitation has decreased across the region. In the early 21st century, dry periods became more pronounced, with the Man-Kendall Z statistic indicating a significant reduction in precipitation in May, July, August, September, and October. The main drought events occurred in 2015-2016 and 2019-2020 across these regions. Keywords: trends; climate variability; Standardized Precipitation-Evapotranspiration Index.